The Influence of Location and Quality of Service on Purchasing Decisions at the 3 Kg LPG Station of Aswandi in Ngabang District Landak Regency - Vhiony Winanda; Samsuddin Samsuddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the effect of location and service quality on purchasing decisions at the Aswandi 3 kg LPG gas station in Ngabang District, Landak Regency. This study was motivated by the increasing competition among LPG distributors and the importance of the role of strategic location and quality service in attracting consumers. This study uses a quantitative approach with an associative research strategy, with a total sample of 100 respondents selected by purposive sampling. Data collection used interviews and questionnaires, while the analysis included validity, reliability, classical assumption tests, and hypothesis testing using IBM SPSS 25. The results showed that location and service quality significantly influenced purchasing decisions. Multiple linear regression analysis shows positive coefficients for location (0.232) and service quality (0.460), which indicate a direct contribution to purchasing decisions. The correlation coefficient (R) of 0.712 indicates a strong relationship between these variables, while the coefficient of determination (R²) indicates that 50.7% of purchasing decisions are explained by location and service quality. The F test confirms the simultaneous influence of these factors. The results of this study highlight the importance of strategic placement and good service in maintaining a competitive advantage in the LPG distribution market. These findings provide valuable insights for business owners to improve customer satisfaction and maintain market position amid increasing competition.